Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Breadtalk Bogor Trade Mall - Utami, Nisa Rahmaniyah; Melati, Melati (Prasetiya Mulya Publishing, 2023)
Manufacturers always want to provide the best products for consumers. One way to improve product quality to meet consumer satisfaction. This research consists of 2 variables, namely product quality (X) and consumer satisfaction (Y). The purpose of this study was to determine the effect of product quality (X) on customer satisfaction (Y)BreadTalkBogorTrade Mall. This study uses quantitative methods with simple regression analysis techniques that use data collection techniques from questionnaires. For this study using the Lemeshow formula where the number of respondents in this study were 100 respondents and processed using the SPSS program. The samples taken in this study were 100 respondents who had purchased products atBreadTalkBogorTrade Mall. The technique used in this study usespurposive sampling withnon random sampling. The hypothesis testing method shows that product quality has a positive and significant effect on consumer satisfaction (H1 is accepted), this can be shown from the T test day with a significance value below 0.05, which is 0.000.